An N-terminal half fragment of the histidine phosphocarrier protein, HPr, is disordered but binds to HPr partners and shows antibacterial properties - Neira, José L.; Palomino-Schätzlein, Martina; Hurtado-Gómez, Estefanía; Ortore, María G.; Falcó, Alberto (Biochimica et biophysica acta. General subjects, 2021)
The phosphotransferase system (PTS) modulates the preferential use of sugars in bacteria. It is formed by a protein cascade in which the first two proteins are general (namely enzyme I, EI, and the histidine phosphocarrier protein, HPr) and the others are sugar-specific permeases; the active site of HPr is His15. The HPr kinase/phosphorylase (HPrK/P), involved in the use of carbon sources in Gram-positive, phopshorylates HPr at a serine. The regulator of sigma D protein (Rsd) also binds to HPr. We are designing specific fragments of HPr, which can be used to interfere with those protein-protein interactions (PPIs), where the intact HPr intervenes. We obtained a fragment (HPr48) comprising the first forty-eight residues of HPr. HPr48 was disordered as shown by fluorescence, far-ultraviolet (UV) circular dichroism (CD), small angle X-ray scattering (SAXS) and nuclear magnetic resonance (NMR). Secondary structure propensities, from the assigned backbone nuclei, further support the unfolded nature of the fragment. However, HPr48 was capable of binding to: (i) the N-terminal region of EI, EIN; (ii) the intact Rsd; and, (iii) HPrK/P, as shown by fluorescence, far-UV CD, NMR and biolayer interferometry (BLI). The association constants for each protein, as measured by fluorescence and BLI, were in the order of the low micromolar range, similar to those measured between the intact HPr and each of the other macromolecules. Although HPr48 is forty-eight-residue long, it assisted antibiotics to exert antimicrobial activity. HPr48 could be used as a lead compound in the development of new antibiotics, or, alternatively, to improve the efficiency of existing ones. [Display omitted] •Isolated HPr48, derived from the histidine phosphocarrier HPr, was disordered.•HPr48 bound to intact proteins involved in phosphorylation and transcription routes.•The affinity of HPr48 for those proteins was the same as that of intact protein.•HPr48 assisted antibiotics to exert antimicrobial activity.